BIR JINSLI BOʻLMAGAN MURAKKAB OSESIMMETRIK JISMDA NOSTATSIONAR ISSIQLIK TARQALISH MASALASINI CHEKLI ELEMENTLAR USULIDA SONLI MODELLASHTIRISH - Sapayev, Sh.O. (SCIENCE and SOCIETY, 2025)
The article develops a numerical model for solving non-stationary problems of heat dissipation in homogeneous and non-homogeneous axisymmetric bodies based on the finite element method, and creates an algorithm and software for solving the problem.